Cognitive Consequence of Obstructive Sleep Apnea Syndrome: A Case Study - Kathy Sexton-Radek (Medical Science: Trends and Innovations Vol. 10, 2025)
Obstructive Sleep Apnea (OSA) is a severe respiratory condition. Patients often present with fatigue and excessive daytime sleepiness. An overnight polysomnographic is used to record the measures of brain waves, muscle tension, heart rate, rate of respiration and temperature to determine stages of sleep. The case of a 62-year-old male illustrated the medical emergent need for treatment. Severe excessive daytime sleepiness and neurocognitive functioning symptoms were evident from his chronic untreated sleepiness. An all-night polysomnogram confirmed the diagnosis of Obstructive Sleep Apnea (OSA). The implication of this case’s chronic untreated experience of OSA is discussed in terms of neurocognitive/brain structure laboratory findings. Results at intake, one and three months of this case’s sleep and cognitive functioning are reported. OSA is treated with CPAP and lifestyle change therapies on a monthly basis. The bimonthly cognitive behavior therapy sessions focused on integrating exercise and good nutrition. The patient was given supportive education about the lifestyle factors that placed him at risk for OSA and after treatment ended, the patient experienced some of the symptoms.